PERSEPSI PENGUNJUNG TERHADAP KUALITAS REST AREA TAMAN GISTING SEBAGAI RUANG PUBLIK - Ferri Anggara Ade Gunawan; Indah Listiana; Yudha Rahman (Jurnal Perencanaan dan Pengembangan Kebijakan, 2021)
Public space is part of the urban element that facilitates the interaction and communication needs of the society and describes the quality of urban space. The provision of public space affects social, economic, environmental and community quality activities, so a quality public space is needed. Parks as public spaces in Tanggamus Regency have not been evenly distributed because they are only available in 3 sub-districts, namely Taman Kota Ir. Soekarno (Kota Agung Pusat District), Rest Area Taman Gisting (Gisting District), and Rest Area Pugung (Pugung District) showed that the provision of public space had not met the distribution and quantity aspects. Rest Area Taman Gisting is located in Gisting Urban, which acts as a public space, so it is necessary to identify its quality because it has to serve the surrounding sub-districts. In addition, the declining quality of facilities and various other problems affect its quality as a public space. This study aims to determine the visitor's perception of the quality of the Gisting Park Rest Area as a public space. This study uses quantitative research methods with descriptive statistical analysis techniques and scoring methods (Likert scale). Based on the results of the study, visitors' perceptions of the quality of the Rest Area Taman Gisting as a public space are sufficient to meet the needs of visitors, sufficient to protect the rights of visitors, and sufficient to provide meaning for visitors. Keywords: Quality, Public Space, Perception